Survival and Integration of Neurons Derived from Human Embryonic Stem Cells in MPTP-Lesioned Primates - Dustin R. Wakeman; Stephanie Weiss; John R. Sladek; John D. Elsworth; Brian Bauereis; Csaba Leranth; Patrick J. Hurley; Robert H. Roth; D. Eugene Redmond (Cell Transplantation, 2014)
A human embryonic stem cell (HESC) line, H1, was studied after differentiation to a dopaminergic phenotype in vitro in order to carry out in vivo studies in Parkinsonian monkeys. To identify morphological characteristics of transplanted donor cells, HESCs were transfected with a GFP lentiviral vector. Gene expression studies were performed at each step of a neural rosette-based dopaminergic differentiation protocol by RT-PCR. In vitro immunofluorescence revealed that >90% of the differentiated cells exhibited a neuronal phenotype by β-III-tubulin immunocytochemistry, with 17% of the cells coexpressing tyrosine hydroxylase prior to implantation. Biochemical analyses demonstrated dopamine release in culture in response to potassium chloride-induced membrane depolarization, suggesting that the cells synthesized and released dopamine. These characterized, HESC-derived neurons were then implanted into the striatum and midbrain of MPTP (1-methyl-4- phenyl-1,2,3,6-tetrahydropyridine)-exposed monkeys that were triple immunosuppressed. Here we demonstrate robust survival of transplanted HESC-derived neurons after 6 weeks, as well as morphological features consistent with polarization, organization, and extension of processes that integrated into the host striatum. Expression of the dopaminergic marker tyrosine hydroxylase was not maintained in HESC-derived neural grafts in either the striatum or substantia nigra, despite a neuronal morphology and expression of β-III-tubulin. These results suggest that dopamine neuronal cells derived from neuroectoderm in vitro will not maintain the correct midbrain phenotype in vivo in nonhuman primates, contrasted with recent studies showing dopamine neuronal survival using an alternative floorplate method.